Bone Marrow Granuloma with Miliary Mottling presenting as Pancytopenia- A rare finding in Tuberculosis - A Case report - Momin, Majed Abdul Basit; Singh, Rahul Dev; C, Ugandhar Bhattu; G, Krishna Mohan Reddy (Mediscope, 2021)
Bone marrow granuloma and miliary mottling presenting as pancytopenia together is a rare finding in disseminated form of tuberculosis. Here we report a case of a 52-year, old male patient presented with generalized weakness, loss of appetite, decreased physical activity for one month. Initial lab hematological investigations revealed pancytopenia and high Erythrocyte sedimentation rate. Bone marrow biopsy was performed to determine the cause of pancytopenia which showed caseating granulomas with positive acid fast bacilli on Ziehl-Neelsen staining (Z-N). In chest X-ray miliary mottling and bone marrow biopsy findings together confirmed the case of disseminated tuberculosis. This unusual presentation highlights the considerable diagnostic challenge and importance of bone marrow biopsy for early diagnosis and initiation of treatment. Mediscope Vol. 8, No. 1: January 2021, Page 63-66